2021
DOI: 10.4103/jfmpc.jfmpc_1480_20
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of self-reported bleeding tendency symptoms among adolescents in Almadinah Almunawwarah, kingdom of Saudi Arabia

Abstract: Bleeding tendency is a common medical problem that is usually caused by either coagulation factors abnormalities, platelets disorders, or vasculopathy. Detection of patients with high bleeding risk through history taking and accurate diagnosis followed by appropriate management will help decreasing chances of significant complications. Methodology: A cross-sectional survey of a random sample of adolescent students in the preparatory year at Taibah University in Almadinah Almunawwarah,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In this study, the prevalence of self-reported epistaxis was 71%. A similar prevalence was recently reported in Saudi Arabia, (Zolaly et al, 2021) which is higher than the prevalence reported in other nations (60%) (Wojak, 2020). The prevalence of epistaxis in this study was significantly higher in men (51.7%) than in women (19.3%; P < 0.0001), which is in agreement with another report from Saudi Arabia (Al-Saleh et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the prevalence of self-reported epistaxis was 71%. A similar prevalence was recently reported in Saudi Arabia, (Zolaly et al, 2021) which is higher than the prevalence reported in other nations (60%) (Wojak, 2020). The prevalence of epistaxis in this study was significantly higher in men (51.7%) than in women (19.3%; P < 0.0001), which is in agreement with another report from Saudi Arabia (Al-Saleh et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Zolaly conducted a study among university students in Medina to assess bleeding tendency, which showed 52.6% had a history of bleeding tendency, with oral cavity bleeding (39.6%) and mucocutaneous bleeding (22.6%) being the most common symptoms reported. This indicated that the cause of these bleeding symptoms can be platelet disorders or VWD [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have highlighted different symptoms of frequent bleeding among the preparatory year students at Taibah University in Almadinah Almunawwarah to understand the prevalence of self-reported bleeding symptoms among adolescents (Zolaly et al, 2021). They collected questionnaires from 680 young participants with an average age of 19 years old, 55.6% of the study participants were female individuals whereas 44.4% were male individuals.…”
Section: National Surveysmentioning
confidence: 99%
“…3.2% have experienced hemarthrosis or muscle hematoma with few seeking special medical intervention. 16.1% of female participants reported heavy menstrual cycles in 6–10 days [ 13 ].…”
Section: National Surveysmentioning
confidence: 99%